Mite Bite Underlying A Lid Swelling - A Rare Presentation Of Scrub Typhus: Life Sciences-Ophthalmology - Subha. L, Dr.; DhilsathRaseena. N, Dr.; Amruthaa, Dr G. (International Journal of Life Science and Pharma Research, 2023)
Scrub Typhus, a vector-borne and zoonotic disease by Orientia tsutsugamushi, is one of the causes of acute febrileillness in India. In endemic regions where Scrub Typhus is prevalent, healthcare providers should keep an eye out and be verysuspicious about this disease, especially when encountering patients with acute febrile illness and exposure to mite-infested areas.Prompt recognition and appropriate diagnostic testing, such as serological assays or molecular methods, are essential for accuratediagnosis. Once diagnosed, treatment with appropriate antibiotics, such as doxycycline or azithromycin, can effectively manageScrub Typhus and prevent complications. Early initiation of treatment is crucial to reduce the chance of severe disease and potentialmortality. This case report highlights the importance of considering Scrub Typhus as a potential differential diagnosis in lid infectionsand acute febrile illnesses, particularly in areas where the disease is endemic. Healthcare providers should be aware of the diverseclinical presentations and remain vigilant to ensure timely and accurate diagnosis, leading to appropriate management and improvedpatient outcomes. Public health efforts should also focus on increasing awareness about Scrub Typhus, its prevention, and earlydetection to minimize the burden of this often underdiagnosed disease. In this case report, we presented a child with febrile illnessand unilateral lid swelling misdiagnosed as stye. The presence of eschar prompted an investigation of Scrub typhus, which waspositive. This case is reported as the lid is an unusual site for eschar formation. To reiterate, scrub typhus should be considered adifferential diagnosis in lid infections and acute febrile illness, particularly in endemic areas.